The practical guide to special education needs in inclusive primary classrooms - Rose, Richard, 1953- (Primary Guides., 2007)
Drawing on recent research and innovation in the education of pupils with special educational needs, this accessible book provides practical examples and advice on how to meet the challenges of developing effective teaching and learning in inclusive settings. With advice on building positive attitudes, developing specific teaching strategies and adapting personalizing teaching approaches, the book helps teachers to build upon their earlier training in both practical and reflective ways.